Self-crosslinking thickening agent for slickwater and preparation method thereof and fracturing fluid
Patent Information
- Application Number
- CN202610500376.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-04-16
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2046-04-16
AI Technical Summary
然而,该文献中并无高分子聚合物,实际上也并不存在交联反应,难以获得增稠性能优异的稠化剂
本发明制得的耐温耐剪切耐盐聚合物含有丰富的阴阳离子,如季铵盐阳离子结构、咪唑基阳离子结构、磺酸根阴离子等,可以通过阴阳离子相互吸引,实现分子缠绕,从而弹性模量增加,提高携砂性能,具备较好的携砂和稠化效果。其中,制备的单体1-乙烯基-3-乙基咪唑溴盐是一种含有碳碳双键的离子液体,由阴离子和有机阳离子构成,在特定条件下可以与其他单体双键共聚,具有优异的热稳定性和导电性,同时,其咪唑基刚性结构也能明显提高聚合物的机械性能和抗剪切性能。本发明制备的单体1含有丰富的磺酸根基团,具有抵抗外界阳离子进攻的能力,有效地增强了聚合物链段的机械性能与耐盐能力,形成了五元环的季铵盐结构不仅提高了聚合物的耐温性能,同时,其刚性的环状结构也提高了聚合物的耐剪切性能,其中等分子量链段结构规整,有效抵抗分子卷曲,使得聚合物在较高黏度下也具备较强的抵抗机械降解的能力。
Smart Images

Figure CN122037906B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of petroleum extraction technology, specifically to a self-crosslinking slickwater thickener, its preparation method, and fracturing fluid. Background Technology
[0002] Thickeners are water-soluble proppant-carrying materials commonly used in fracturing technology for oilfield reservoir stimulation. The effectiveness of fracturing in oilfield reservoirs depends on the performance of both the thickener and the fracturing fluid. Therefore, the performance of the thickener (dissolution rate and solution viscosity) is crucial in determining the quality of fracturing operations. Polyacrylamide (PAM) or polyacrylamide copolymers, with their good water solubility, high aqueous solution viscosity, and stable chemical properties, are commonly used as a major component in thickeners for fracturing operations. The dissolution rate of the thickener is also related to its supply form (dry powder, suspension, or emulsion). In dry powder and suspension thickeners, the PAM or PAM copolymer particles are larger, and the interactions between molecular chains are stronger, resulting in a slower water dissolution rate. However, although emulsion-type PAM thickeners have small particle sizes (nanoscale, 50-200 nm), resulting in shorter dissolution times and faster solution viscosity in water, the solid content of PAM is generally lower, the flexibility of formulation adjustment is poor, and the salt resistance and stability of the aqueous solution are relatively poor. In addition, dry powder PAM thickeners have poor dispersibility in water and are prone to producing "fish eyes" (PAM solution encapsulating PAM dry powder particles) during the dissolution process, which makes their dissolution time in water too long and does not meet the requirements for continuous construction.
[0003] Traditional polymer thickeners are mainly in powder form, which requires full swelling before use. This prolongs the construction operation time and increases the cost of fracturing fluid preparation. In addition, most polymer thickeners require the addition of cross-linking agents to form a relatively dense spatial configuration and thus exert a better thickening effect. However, if the cross-linking agent is not well compatible with the thickener system, it may adversely affect the overall thickening performance of the thickener. This obviously increases the difficulty of using fracturing fluid and the operating cost.
[0004] Chinese invention patent application CN110437817A discloses a multifunctional emulsion-type salt-resistant fracturing fluid and its preparation method. The multifunctional fracturing fluid described in this patent uses a large number of additives, including drainage aids, clay stabilizers, crosslinking agents, polymer destructors, and polymer destructor aids. The construction process is complex and involves many procedures, which increases its cost.
[0005] Chinese invention patent application CN110467911A discloses a salt-resistant multifunctional fracturing fluid and its preparation method. In order to increase its sand-suspending performance, this patent requires the use of additives and crosslinking agents to improve its performance, which increases the difficulty of construction and labor costs. In addition, it adds demulsifiers, resulting in a wide variety of additives and complex construction.
[0006] The two patents mentioned above are not easy to construct and have high costs, requiring additives and crosslinking agents to suspend sand.
[0007] Chinese invention patent application CN103773354A discloses a surfactant-based thickener for fracturing fluids, composed of a surfactant, a counterionic salt, a potassium salt of an organic acid, an organic acid, C1-C3 alcohols, and water. The base fluid can be clean water, 1-3 wt% acid, or mineralized water with a salinity of less than 50,000 mg / L. The thickener undergoes online crosslinking, eliminating the need for pre-mixing and meeting the requirements of large-scale horizontal well multi-stage fracturing, enabling factory-scale operations. However, this document does not mention any high-molecular polymers, and in reality, no crosslinking reaction occurs, making it difficult to obtain a thickener with excellent thickening properties. Summary of the Invention
[0008] The purpose of this invention is to propose a self-crosslinking slickwater thickener, its preparation method, and fracturing fluid. The prepared self-crosslinking slickwater thickener has excellent temperature resistance, salt resistance, and shear resistance, as well as good thickening and dissolving properties, and good proppant carrying and thickening effects. It has a low damage rate to the core after breaking the gel and can be widely used in the fracturing stimulation of low-permeability and ultra-low-permeability reservoirs. The fracturing fluid obtained integrates functions such as drag reduction, proppant carrying, fracture creation, swelling prevention, drainage assistance, and low damage, and has broad application prospects.
[0009] The technical solution of this invention is implemented as follows: This invention provides a self-crosslinking thickener for slippery water, comprising a heat-resistant, shear-resistant, and salt-resistant polymer, a synergist, a salt-resistant component, a structure modifier, a suspending agent, and an emulsifier; The temperature-, shear-, and salt-resistant polymer has the structure shown in Formula I: Formula I; Where a:b:c:d=12-15:20-40:10-15:7-10, n=3-5.
[0010] As a further improvement of the present invention, the mass ratio of the temperature-resistant, shear-resistant, and salt-resistant polymer, synergist, salt-resistant component, structure modifier, suspending agent, and emulsifier is 50-70:2-4:1-2:3-5:3-5:2-3; the synergist is selected from at least one of sodium p-aminobenzenesulfonate and fluorinated surfactants; the salt-resistant component is sodium 2-acrylamido-2-methylpropanesulfonate or N-benzyl-N-acryloylamino-alkyl sulfonate; the structure modifier is ethylene glycol methyl ether or ethylene glycol butyl ether; the suspending agent is selected from at least one of fumed silica, organobentonite, and montmorillonite; and the emulsifier is a Span series or Tween series emulsifier.
[0011] As a further improvement of the present invention, the temperature-, shear-, and salt-resistant polymer is prepared from monomer 1, acrylamide, sodium 2-acrylamido-2-methylpropanesulfonate, and 1-vinyl-3-ethylimidazolium bromide in a mass ratio of 63-92:14-29:22-35:14-21; the structural formula of monomer 1 is shown in Formula II: Formula II; Where n = 3 - 5.
[0012] As a further improvement of the present invention, the method for preparing monomer 1 is as follows: S1. Reaction of ethylene glycol ether with thionyl chloride yields intermediate 1, with the following structure: ; S2. Diallylamine was reacted with sodium 3-chloro-2-hydroxypropanesulfonate to prepare intermediate 2, with the following structure: ; S3. Intermediate 2 is reacted with intermediate 1 to obtain intermediate 3, with the following structure: ; S4. Intermediate 3 is reacted with butanesulfonyl lactone to prepare monomer 1.
[0013] As a further improvement of the present invention, in step S1, the molar ratio of ethylene glycol ether to sulfoxide is 1.1-1.2:1, the reaction temperature is room temperature, and the reaction time is 0.5-1 h. The ethylene glycol ether is selected from at least one of triethylene glycol, tetraethylene glycol, and pentaethylene glycol. In step S2, the molar ratio of diallylamine to sodium 3-chloro-2-hydroxypropanesulfonate is 1.2-1.5:1, and an alkali is added, namely NaOH or KOH. The reaction temperature is 65-75°C, and the reaction time is 4-6 h.
[0014] As a further improvement of the present invention, in step S3, the molar ratio of intermediate 2 to intermediate 1 is 1.2-1.5:1, and an alkali is added, wherein the alkali is selected from at least one of triethylamine, NaOH, and KOH, and the reaction temperature is 40-50°C for 2-4 hours; in step S4, the molar ratio of intermediate 3 to butane sulpholactone is 1:1.2-1.5, the reaction temperature is 50-60°C, and the reaction time is 20-24 hours.
[0015] As a further improvement of the present invention, the preparation method of the temperature-resistant, shear-resistant, and salt-resistant polymer is as follows: Monomer 1, acrylamide, sodium 2-acrylamido-2-methylpropanesulfonate, and 1-vinyl-3-ethylimidazolium bromide are dissolved in water, and NaOH is added to adjust the solution to neutral, so as to prepare an aqueous solution with a total monomer concentration of 35-37 wt%; then, under inert gas protection, an initiator and water are added to make the total monomer concentration 27-32 wt%, the reaction is heated and stirred, cooled to room temperature, purified, cut, dried, and pulverized to obtain the temperature-resistant, shear-resistant, and salt-resistant polymer.
[0016] As a further improvement of the present invention, the initiator is selected from at least one of sodium persulfate, potassium persulfate, and ammonium persulfate, and the amount added is 1-2 wt% of the total mass of the system. The temperature of the heating and stirring reaction is 50-60°C, and the time is 3-5 h.
[0017] The present invention further protects the preparation of the above-mentioned self-crosslinking thickener for slippery water, comprising the following steps: stirring and mixing a heat-resistant, shear-resistant, and salt-resistant polymer, an emulsifier, and a suspending agent; adding a synergist, a salt-resistant component, and a structure modifier; dispersing and mixing evenly to obtain a self-crosslinking thickener for slippery water.
[0018] This invention further protects a self-crosslinking slickwater fracturing fluid, which is prepared from the following raw materials in the following mass percentages: 0.05-0.3% of the above-mentioned self-crosslinking slickwater thickener, 0.1-0.5% of the clay stabilizer, 0.1-0.5% of the drainage aid, and the balance being water.
[0019] The present invention has the following beneficial effects: The temperature-, shear-, and salt-resistant polymer prepared in this invention contains abundant anions and cations, such as quaternary ammonium salt cation structures, imidazole group cation structures, and sulfonate anions. These anions and cations attract each other, achieving molecular entanglement, thereby increasing the elastic modulus, improving sand-carrying capacity, and exhibiting good sand-carrying and thickening effects. The prepared monomer 1-vinyl-3-ethylimidazolium bromide is an ionic liquid containing carbon-carbon double bonds, composed of anions and organic cations. Under specific conditions, it can copolymerize with other monomer double bonds, exhibiting excellent thermal stability and electrical conductivity. Simultaneously, its imidazole group rigid structure significantly improves the polymer's mechanical properties and shear resistance. The monomer 1 prepared in this invention contains abundant sulfonate groups, possessing the ability to resist external cation attack, effectively enhancing the mechanical properties and salt resistance of the polymer segments. The five-membered ring quaternary ammonium salt structure not only improves the polymer's temperature resistance but also its rigid cyclic structure enhances its shear resistance. The regular structure of the isomeric segments effectively resists molecular coiling, enabling the polymer to possess strong resistance to mechanical degradation even at high viscosity.
[0020] This invention, by adding inorganic particle suspending agents, can form hydrogen bonds and van der Waals forces with the abundant anions and cations in temperature-resistant, shear-resistant, and salt-resistant polymers, thus acting as physical cross-linking points and improving the viscosity and sand-carrying capacity of the thickener.
[0021] The self-crosslinking slickwater thickener prepared by this invention has excellent temperature resistance, salt resistance, and shear resistance. It also has good thickening and dissolving properties, as well as good sand carrying and thickening effects. After breaking the gel, it causes low damage to the core and can be widely used in the fracturing of low-permeability and ultra-low-permeability reservoirs. The fracturing fluid prepared integrates functions such as drag reduction, sand carrying, fracture creation, swelling prevention, drainage assistance, and low damage, and has broad application prospects. Attached Figure Description
[0022] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0023] Figure 1 Infrared spectrum of the heat-resistant, shear-resistant, and salt-resistant polymer prepared in Example 4.
[0024] Figure 2 The SEM microstructure of the temperature-resistant, shear-resistant, and salt-resistant polymer prepared in Example 4 is shown in clean water. Detailed Implementation
[0025] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0026] Preparation Example 1: Preparation of Monomer 1 The method is as follows: S1. Dissolve 0.11 mol of triethylene glycol in 200 mL of dichloromethane, add 0.1 mol of sulfoxide at 0 °C, restore to room temperature, stir for 0.5 h, remove solvent under reduced pressure, wash, filter, and dry to obtain intermediate 1; ESI-MS calculated value: C6H 14 ClO3(M+H) + 169.62, measured value: 169.6, yield: 89%. NMR results: 1 H NMR (300MHz, CDCl3) δ3.65-3.7 (m, 4H), 3.5-3.55 (m, 8H), 2.1 (br, 1H).
[0027] S2. Dissolve 0.1 mol of sodium 3-chloro-2-hydroxypropanesulfonate in 100 mL of ethylene glycol by heating. Heat to 65 °C, add 0.12 mol of diallylamine, adjust the pH of the mixed solution to 8.5 with 40% KOH aqueous solution, stir for 4 h, and purify to obtain intermediate 2; ESI-MS calculated value: C9H 17 NNaO4S(M+H) + 258.28, measured value: 258.3, yield: 78%. NMR results: 1 H NMR (300MHz, CDCl3) δ5.81 (m, 2H), 5.15-5.18 (m, 4H), 3.51-3.53 (m, 2H), 3.46 (m, 1H), 3.01 (s, 4H), 2.68 (m, d, 2H), 2.2 (br, 1H).
[0028] S3. Dissolve 0.12 mol of intermediate 2, 0.1 mol of intermediate 1, and 0.3 mol of triethylamine in 200 mL of acetonitrile, heat to 40 °C, stir for 2 h, purify, wash, and dry to obtain intermediate 3; ESI-MS calculated value: C 15 H 29 NNaO7S(M+H) + 390.44, measured value: 390.4, yield: 82%. NMR results: 1 H NMR (300MHz, CDCl3) δ5.89 (m, 2H), 5.12-5.15 (m, 4H), 3.66-3.72 (m, 4H), 3.51-3.57 (m, 10H), 3.03-3.10 (m, 5H), 2.3-2.4 (m, 2H), 2.3 (br, 1H).
[0029] S4. Dissolve 0.1 mol of intermediate 3 and 0.12 mol of butanesulfonyl lactone in 200 mL of acetone, heat to 50 °C, stir and react for 20 h, recrystallize from methanol and petroleum ether at a volume ratio of 5:1, filter, wash, and dry to obtain monomer 1. ESI-MS calculated value: C 19 H 37 NNaO 10 S2(M+H) + 526.62, measured value: 526.6, yield: 78%. NMR results: 1H NMR (300MHz, CDCl3) δ5.82 (m, 2H), 5.10-5.14 (m, 4H), 3.91-3.93 (t, 2H), 3.61-3.70 (m, 4H) , 3.48-3.59 (m, 12H), 3.05-3.12 (m, 5H), 2.35-2.42 (m, 2H), 2.2 (br, 1H), 1.72-1.80 (m, 4H).
[0030] Preparation Example 2: Preparation of Monomer 1 The method is as follows: S1. Dissolve 0.12 mol tetrapentaethylene glycol in 200 mL dichloromethane, add 0.1 mol dichloro sulfoxide at 0 °C, restore to room temperature, stir for 1 h, remove solvent under reduced pressure, wash, filter, and dry to obtain intermediate 1; S2. Dissolve 0.1 mol of sodium 3-chloro-2-hydroxypropanesulfonate in 100 mL of ethylene glycol by heating. Heat to 75 °C, add 0.15 mol of diallylamine, adjust the pH of the mixed solution to 8.5 with 40% NaOH aqueous solution, stir for 6 h, purify, and obtain intermediate 2. S3. Dissolve 0.15 mol of intermediate 2, 0.1 mol of intermediate 1, and 0.3 mol of triethylamine in 200 mL of acetonitrile, heat to 50 °C, stir and react for 4 h, purify, wash, and dry to obtain intermediate 3; S4. Dissolve 0.1 mol of intermediate 3 and 0.15 mol of butane sulfonyl lactone in 200 mL of acetone, heat to 60 °C, stir and react for 24 h, recrystallize from methanol and petroleum ether at a volume ratio of 5:1, filter, wash and dry to obtain monomer 1 with an overall yield of 75.5%.
[0031] Preparation Example 3: Preparation of Monomer 1 The method is as follows: S1. Dissolve 0.115 mol of tetraethylene glycol in 200 mL of dichloromethane, add 0.1 mol of thionyl chloride at 0 °C, restore to room temperature, stir for 1 h, remove solvent under reduced pressure, wash, filter, and dry to obtain intermediate 1; S2. Dissolve 0.1 mol of sodium 3-chloro-2-hydroxypropanesulfonate in 100 mL of ethylene glycol by heating. Heat to 70 °C, add 0.135 mol of diallylamine, adjust the pH of the mixed solution to 8.5 with 40% NaOH aqueous solution, stir for 5 h, purify, and obtain intermediate 2. S3. Dissolve 0.135 mol of intermediate 2, 0.1 mol of intermediate 1, and 0.3 mol of triethylamine in 200 mL of acetonitrile, heat to 45 °C, stir and react for 3 h, purify, wash, and dry to obtain intermediate 3; S4. Dissolve 0.1 mol of intermediate 3 and 0.135 mol of butane sulfonyl lactone in 200 mL of acetone, heat to 55 °C, stir and react for 22 h, recrystallize with methanol and petroleum ether at a volume ratio of 5:1, filter, wash and dry to obtain monomer 1 with an overall yield of 74.8%.
[0032] Preparation Example 4: Preparation of Temperature-Resistant, Shear-Resistant, and Salt-Resistant Polymers The method is as follows: 63 parts by weight of monomer 1 obtained from Preparation Example 1, 14 parts by weight of acrylamide, 22 parts by weight of sodium 2-acrylamido-2-methylpropanesulfonate, and 14 parts by weight of 1-vinyl-3-ethylimidazolium bromide were dissolved in water, and NaOH was added to adjust the solution to neutral to prepare an aqueous solution with a total monomer concentration of 35 wt%. Then, under nitrogen protection, potassium persulfate and water were added, with the amount of potassium persulfate added being 1 wt% of the total mass of the system, so that the total monomer concentration was 27 wt%. The mixture was heated to 50°C, stirred for 3 hours, cooled to room temperature, purified, shredded, dried, and pulverized to obtain a heat-resistant, shear-resistant, and salt-resistant polymer.
[0033] Depend on Figure 1 It can be seen that at 3415cm -1 The peak at 3170 cm⁻¹ represents the stretching vibration peak of NH₄⁺ on quaternary ammonium salts. -1 The characteristic absorption peak of the amide group -NH is at 3105 cm⁻¹. -1 The absorption peak at 2911 cm⁻¹ represents the CO ether bond. -1 The peak at 1572 cm⁻¹ represents the CH stretching vibration of the alkyl chain. -1 The peak at 1122 cm⁻¹ represents the stretching vibration of the C=O group in the amide group, while the peak at 1487 cm⁻¹ represents the bending vibration of the CH group in the alkyl chain. -1 The absorption peak at 957 cm⁻¹ is the stretching vibration of the sulfonic acid group -SO₃; -1 The peak at 759 cm⁻¹ is due to the in-plane rocking and bending vibration of the CH group on the imidazole ring. -1 The peak at 672 cm⁻¹ is caused by the out-of-plane rocking and bending vibration of the CH group on the imidazole ring. -1 The absorption peak for CS is located at 995-985 cm⁻¹. Additionally, there is an absorption peak in the range of 995-985 cm⁻¹. -1 With 915-905cm -1 The absence of an out-of-plane bending vibration absorption peak for the =CH group of the alkene indicates that the double bond in the C=C group has already undergone a reaction.
[0034] Depend on Figure 2 It can be seen that the heat-resistant, shear-resistant, and salt-resistant polymers diffuse uniformly in aqueous solutions, forming a spatial network structure.
[0035] Preparation Example 5: Preparation of Temperature-Resistant, Shear-Resistant, and Salt-Resistant Polymers like Figure 2The method is as follows: 92 parts by weight of monomer 1 obtained from Preparation Example 2, 29 parts by weight of acrylamide, 35 parts by weight of sodium 2-acrylamido-2-methylpropanesulfonate, and 21 parts by weight of 1-vinyl-3-ethylimidazolium bromide were dissolved in water, and NaOH was added to adjust the solution to neutral to prepare an aqueous solution with a total monomer concentration of 37 wt%. Then, under nitrogen protection, ammonium persulfate and water were added, with the amount of ammonium persulfate added being 2 wt% of the total mass of the system, so that the total monomer concentration was 32 wt%. The mixture was heated to 60°C, stirred for 5 hours, cooled to room temperature, purified, shredded, dried, and pulverized to obtain a heat-resistant, shear-resistant, and salt-resistant polymer.
[0036] Preparation Example 6: Preparation of Temperature-Resistant, Shear-Resistant, and Salt-Resistant Polymers like Figure 2 The method is as follows: 74 parts by weight of monomer 1 obtained from Preparation Example 3, 22 parts by weight of acrylamide, 28 parts by weight of sodium 2-acrylamido-2-methylpropanesulfonate, and 19 parts by weight of 1-vinyl-3-ethylimidazolium bromide were dissolved in water, and NaOH was added to adjust the solution to neutral to prepare an aqueous solution with a total monomer concentration of 36 wt%. Then, under nitrogen protection, sodium persulfate and water were added, with the amount of sodium persulfate added being 1.5 wt% of the total mass of the system, so that the total monomer concentration was 30 wt%. The mixture was heated to 55°C, stirred for 4 hours, cooled to room temperature, purified, shredded, dried, and pulverized to obtain a heat-resistant, shear-resistant, and salt-resistant polymer.
[0037] Comparative Preparation Example 1 The difference from Preparation Example 6 is that monomer 1 was not added.
[0038] Comparative Preparation Example 2 The difference from Preparation Example 6 is that sodium 2-acrylamido-2-methylpropanesulfonate was not added.
[0039] Comparative preparation example 3 The difference from Preparation Example 6 is that 1-vinyl-3-ethylimidazolium bromide was not added.
[0040] Example 1; This example provides a preparation of a self-crosslinking thickener for slippery water, comprising the following steps: 50 parts by weight of the heat-resistant, shear-resistant, and salt-resistant polymer obtained in Preparation Example 4, 2 parts by weight of Tween-80, and 3 parts by weight of montmorillonite are stirred and mixed for 15 min, 2 parts by weight of fluorocarbon surfactant FC-3, 1 part by weight of N-benzyl-N-acryloylamino-alkyl sulfonate, and 3 parts by weight of ethylene glycol butyl ether are added, and the mixture is stirred and mixed at 1000 r / min for 20 min to obtain the self-crosslinking thickener for slippery water.
[0041] Example 2; This example provides a preparation of a self-crosslinking thickener for slippery water, comprising the following steps: 70 parts by weight of the heat-resistant, shear-resistant, and salt-resistant polymer obtained in Preparation Example 5, 3 parts by weight of Span-80, and 5 parts by weight of organobentonite are stirred and mixed for 15 min, then 4 parts by weight of sodium p-aminobenzenesulfonate, 2 parts by weight of sodium 2-acrylamide-2-methylpropanesulfonate, and 5 parts by weight of ethylene glycol methyl ether are added, and the mixture is stirred and mixed at 1000 r / min for 20 min to obtain the self-crosslinking thickener for slippery water.
[0042] Example 3; This example provides a preparation of a self-crosslinking thickener for slippery water, comprising the following steps: 60 parts by weight of the heat-resistant, shear-resistant, and salt-resistant polymer obtained in Preparation Example 6, 1.5 parts by weight of Tween-80, 1 part by weight of Span-80, and 4 parts by weight of fumed silica are stirred and mixed for 15 min; 3 parts by weight of sodium p-aminobenzenesulfonate, 1.5 parts by weight of sodium 2-acrylamide-2-methylpropanesulfonate, and 4 parts by weight of ethylene glycol methyl ether are added; the mixture is stirred and mixed at 1000 r / min for 20 min to obtain the self-crosslinking thickener for slippery water.
[0043] Comparative Examples 1-3 The difference from Example 3 is that the heat-resistant, shear-resistant, and salt-resistant polymer was prepared by comparative preparation examples 1-3.
[0044] Test Example 1 The self-crosslinking slippery waters prepared in Examples 1-3 and Comparative Examples 1-3 were tested for performance using a thickener. The results are shown in Table 1.
[0045] Thickening performance test The samples were prepared into 0.1 wt% aqueous solutions, and their apparent viscosities were measured using a six-speed rotational viscometer at room temperature (25°C) and 170 s⁻¹. -1 Measurement at shear rate.
[0046] Salt resistance test A 0.1 wt% aqueous solution was prepared, with the mass fraction controlled at 0.5%. NaCl and CaCl2 were added in a molar ratio of 1:1, with the NaCl concentration being 1 wt%. The apparent viscosity of the solution was measured using a six-speed rotational viscometer, with the conditions controlled at room temperature (25℃) and 170 s. -1 The shear rate.
[0047] Temperature resistance test Each solution was prepared into a 0.1 wt% aqueous solution. The apparent viscosity of the solution at 170°C was measured using a six-speed rotational viscometer, with the shear rate controlled at 170 s⁻¹. -1 .
[0048] Shear resistance test Each was prepared into a 0.1 wt% aqueous solution and subjected to continuous shearing using a six-speed rotational viscometer for 1 hour, with the conditions controlled at room temperature (25°C) and 1024 s. -1 The shear rate.
[0049] Table 1 ; As can be seen from the table above, the self-crosslinking thickeners for slick water prepared in Examples 1-3 of the present invention have good thickening, temperature resistance, shear resistance and salt resistance properties.
[0050] Example 4; A self-crosslinking slickwater fracturing fluid, characterized in that it is prepared from the following raw materials in the following mass percentages: 0.05% of the self-crosslinking slickwater thickener obtained in Example 1, 0.1% of the clay stabilizer SRCS-1, 0.1% of the drainage aid SRCU-1, and the balance being water.
[0051] Example 5; A self-crosslinking slickwater fracturing fluid, characterized in that it is prepared from the following raw materials in the following mass percentages: 0.1% of the self-crosslinking slickwater thickener obtained in Example 2, 0.5% of the clay stabilizer SRCS-1, 0.5% of the drainage aid SRCU-1, and the balance being water.
[0052] Example 6; A self-crosslinking slickwater fracturing fluid, characterized in that it is prepared from the following raw materials in the following mass percentages: 0.07% of the self-crosslinking slickwater thickener obtained in Example 3, 0.3% of the clay stabilizer SRCS-1, 0.3% of the drainage aid SRCU-1, and the balance being water.
[0053] Comparative Examples 4-6 The difference from Example 6 is that the thickener for the self-crosslinking slippery water was prepared from Comparative Examples 1-3.
[0054] Test Example 2 The basic performance of the self-crosslinking slickwater fracturing fluids prepared in Examples 4-6 and Comparative Examples 4-6, as well as commercially available similar products, was evaluated in the laboratory according to the evaluation methods and standards of SY / T6376-2008 "General Technical Conditions for Fracturing Fluids".
[0055] 1. Determination of suspended sediment performance The settling velocity of sand particles in self-crosslinked slickwater fracturing fluid was determined using a static suspension test. Self-crosslinked slickwater fracturing fluid was poured into a 100ml graduated cylinder, and the liquid level height h was measured with a ruler. Selected quartz sand was gently placed onto the liquid surface, and a stopwatch was started to record the time t when the first particle reached the bottom of the graduated cylinder. The sand ratio was 20%. The results are shown in Table 2. The settling velocity was calculated as follows: Settling velocity v = Liquid level height / Settling time = h / t.
[0056] Table 2 ; As can be seen from the table above, the self-crosslinking slickwater fracturing fluids prepared in Examples 4-6 of this invention have good sand-carrying capacity.
[0057] Filtration performance test Static filtration loss of self-crosslinking slickwater fracturing fluid was determined at 80℃. The results are shown in Table 3.
[0058] Table 3 ; As shown in the table above, the self-crosslinking slickwater fracturing fluids prepared in Examples 4-6 of this invention have good filtration performance and can meet the requirements for field use.
[0059] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A self-crosslinking thickener for slippery water, characterized in that, The product comprises a heat-, shear-, and salt-resistant polymer, a synergist, a salt-resistant component, a structure modifier, a suspending agent, and an emulsifier; the mass ratio of the heat-, shear-, and salt-resistant polymer, synergist, salt-resistant component, structure modifier, suspending agent, and emulsifier is 50-70:2-4:1-2:3-5:3-5:2-3; the synergist is selected from at least one of sodium p-aminobenzenesulfonate and fluorinated surfactants; the salt-resistant component is sodium 2-acrylamido-2-methylpropanesulfonate or N-benzyl-N-acryloylamino-alkyl sulfonate; the structure modifier is ethylene glycol methyl ether or ethylene glycol butyl ether; the suspending agent is selected from at least one of fumed silica, organobentonite, and montmorillonite; and the emulsifier is a Span series or Tween series emulsifier. The temperature-, shear-, and salt-resistant polymer has the structure shown in Formula I: Equation I; Where a:b:c:d=12-15:20-40:10-15:7-10, n=3-5.
2. The self-crosslinking thickener for slippery water according to claim 1, characterized in that, The temperature-, shear-, and salt-resistant polymer is prepared from monomer 1, acrylamide, sodium 2-acrylamido-2-methylpropanesulfonate, and 1-vinyl-3-ethylimidazolium bromide in a mass ratio of 63-92:14-29:22-35:14-21; the structural formula of monomer 1 is shown in Formula II. Formula II; Where n = 3 - 5.
3. The self-crosslinking thickener for slippery water according to claim 2, characterized in that, The preparation method of monomer 1 is as follows: S1. Reaction of ethylene glycol ether with thionyl chloride yields intermediate 1, with the following structure: ; S2. Diallylamine was reacted with sodium 3-chloro-2-hydroxypropanesulfonate to prepare intermediate 2, with the following structure: ; S3. Intermediate 2 is reacted with intermediate 1 to obtain intermediate 3, with the following structure: ; S4. Intermediate 3 is reacted with butanesulfonyl lactone to prepare monomer 1.
4. The self-crosslinking thickener for slippery water according to claim 3, characterized in that, In step S1, the molar ratio of ethylene glycol ether to sulfoxide is 1.1-1.2:1, the reaction temperature is room temperature, and the reaction time is 0.5-1 h. The ethylene glycol ether is selected from at least one of triethylene glycol, tetraethylene glycol, and pentaethylene glycol. In step S2, the molar ratio of diallylamine to sodium 3-chloro-2-hydroxypropanesulfonate is 1.2-1.5:1, and an alkali is added, namely NaOH or KOH. The reaction temperature is 65-75°C, and the reaction time is 4-6 h.
5. The self-crosslinking thickener for slippery water according to claim 3, characterized in that, In step S3, the molar ratio of intermediate 2 to intermediate 1 is 1.2-1.5:1, and an alkali is added, wherein the alkali is selected from at least one of triethylamine, NaOH, and KOH, and the reaction temperature is 40-50℃ for 2-4 hours; in step S4, the molar ratio of intermediate 3 to butane sulcolone is 1:1.2-1.5, the reaction temperature is 50-60℃ for 20-24 hours.
6. The self-crosslinking thickener for slippery water according to claim 1, characterized in that, The preparation method of the temperature-resistant, shear-resistant, and salt-resistant polymer is as follows: Monomer 1, acrylamide, sodium 2-acrylamido-2-methylpropanesulfonate, and 1-vinyl-3-ethylimidazolium bromide are dissolved in water, and NaOH is added to adjust the solution to neutral to prepare an aqueous solution with a total monomer concentration of 35-37 wt%; then, under inert gas protection, an initiator and water are added to make the total monomer concentration 27-32 wt%, the reaction is heated and stirred, cooled to room temperature, purified, cut, dried, and pulverized to obtain the temperature-resistant, shear-resistant, and salt-resistant polymer.
7. The self-crosslinking thickener for slippery water according to claim 6, characterized in that, The initiator is selected from at least one of sodium persulfate, potassium persulfate, and ammonium persulfate, and the amount added is 1-2 wt% of the total mass of the system. The heating and stirring reaction is carried out at a temperature of 50-60℃ for 3-5 hours.
8. A method for preparing a self-crosslinking thickener for slippery water as described in any one of claims 1-7, characterized in that, Includes the following steps: A heat-resistant, shear-resistant, and salt-resistant polymer, emulsifier, and suspending agent are stirred and mixed. A synergist, salt-resistant component, and structure modifier are added and dispersed and mixed evenly to prepare a self-crosslinking slick thickener.
9. A self-crosslinking slickwater fracturing fluid, characterized in that, It is prepared from the following raw materials in the following mass percentages: 0.05-0.3% of the self-crosslinking slick thickener as described in any one of claims 1-7, 0.1-0.5% of the clay stabilizer, 0.1-0.5% of the drainage aid, and the balance being water.
Citation Information
Patent Citations
Thickening agent applicable to surfactant fracturing liquid and online cross-linking factory operation method
CN103773354A
Multifunctional emulsion-type salt-tolerant fracturing fluid and production method thereof
CN110437817A
Salt-resistant multifunctional fracturing fluid and preparation method thereof
CN110467911A
Integrated variable-viscosity salt-tolerant resistance reducing agent and preparation method thereof
CN111410949A
Thickening agent for oil field fracturing fluid, preparation method of thickening agent and fracturing fluid
CN121852035A
